Compensatory trans-regulatory alleles minimizing variation in TDH3 expression are common within Saccharomyces cerevisiae. Issue 5 (1st October 2019) - Metzger, Brian P. H.; Wittkopp, Patricia J.
Abstract: Heritable variation in gene expression is common within species. Much of this variation is due to genetic differences outside of the gene with altered expression and is trans -acting. This trans -regulatory variation is often polygenic, with individual variants typically having small effects, making the genetic architecture and evolution of trans -regulatory variation challenging to study. Consequently, key questions about trans -regulatory variation remain, including the variability of trans -regulatory variation within a species, how selection affects trans -regulatory variation, and how trans -regulatory variants are distributed throughout the genome and within a species. To address these questions, we isolated and measured trans -regulatory differences affecting TDH3 promoter activity among 56 strains of Saccharomyces cerevisiae, finding that trans -regulatory backgrounds varied approximately twofold in their effects on TDH3 promoter activity. Comparing this variation to neutral models of trans -regulatory evolution based on empirical measures of mutational effects revealed that despite this variability in the effects of trans -regulatory backgrounds, stabilizing selection has constrained trans- regulatory differences within this species. Using a powerful quantitative trait locus mapping method, we identified ∼100 trans -acting expression quantitative trait locus in each of three crosses to a common reference strain, indicating that regulatory variation is more polygenic than previous studies have suggested. Loci altering expression were located throughout the genome, and many loci were strain specific. This distribution and prevalence of alleles is consistent with recent theories about the genetic architecture of complex traits. In all mapping experiments, the nonreference strain alleles increased and decreased TDH3 promoter activity with similar frequencies, suggesting that stabilizing selection maintained many trans -acting variants with opposing effects. This variation may provide the raw material for compensatory evolution and larger scale regulatory rewiring observed in developmental systems drift among species.